Pengaruh Blended Learning Pada Pembelajaran Matematika (Tinjauan Meta-Analisis) - Banunaek, Imanuel Mesakh Andreas (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to determine the effect of Blended Learning on student learning outcomes and to determine the difference in the effect of Blended Learning on student learning outcomes based on education level. This research is a systematic literature review using meta-analysis. The research sample was 6 experimental research articles using BL published in scientific journals between 2015-2022. The calculation of the effect size used eta-squared and Cohen's d formula. The findings of this study reveal that the Blended Learning has an influence on mathematics learning outcomes, where there are 3 articles with a very high effect size category, 1 article with a high effect size category, 1 article with a medium effect size category, and 1 article with a low effect size. Overall, it was found that the Blended Learning had a high influence on mathematics learning outcomes with an average EZ of 1.83. There is a difference in the effect of using the Blended Learning on mathematics learning outcomes based on the education level